The Dark Knight rises [videorecording (DVD)] - Nolan, Christopher, 1970-; Bale, Christian, 1974-; Hathaway, Anne, 1982-; Hardy, Tom, 1977-; Oldman, Gary; Cotillard, Marion, 1975-; Gordon-Levitt, Joseph, 1981-; Freeman, Morgan; Caine, Michael (Warner Bros. Entertainment, 2012)
It has been eight years since Batman vanished into the night, turning, in that instant, from hero to fugitive. Assuming the blame for the death of D.A. Harvey Dent, the Dark Knight sacrificed everything for what he and Commissioner Gordon both hoped was the greater good. For a time the lie worked, as criminal activity in Gotham City was crushed under the weight of the anti-crime Dent Act.